Posidonia oceanica as a Source of Chromophoric Dissolved Organic Matter for the Oligotrophic NW Mediterranean Coast - Francesca Iuculano; Carlos M. Duarte; Jaime Otero; Xosé Antón Álvarez-Salgado; Susana Agustí (Journal of Marine Science and Engineering, 2020)
Posidonia oceanica is a well-recognized source of dissolved organic matter (DOM) derived from exudation and leaching of seagrass leaves, but little is known about its impact on the chromophoric fraction of DOM (CDOM). In this study, we monitored for two years the optical properties of CDOM in two contrasting sites in the Mallorca Coast (Balearic Islands). One site was a rocky shore free of seagrass meadows, and the second site was characterized by the accumulation of non-living seagrass material in the form of banquettes. On average, the integrated color over the 250–600 nm range was almost 6-fold higher in the beach compared with the rocky shore. Furthermore, the shapes of the CDOM spectra in the two sites were also different. A short incubation experiment suggested that the spectral differences were due to leaching from P. oceanica leaf decomposition. Furthermore, occasionally the spectra of P. oceanica was distorted by a marked absorption increase at wavelength < 265 nm, presumably related to the release of hydrogen sulfide (HS−) associated with the anaerobic decomposition of seagrass leaves within the banquettes. Our results provide the first evidence that P. oceanica is a source of CDOM to the surrounding waters.